2013
DOI: 10.4067/s0718-58392013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Growth, yield, and fruit quality of ‘Rhode red Valencia’ and ‘Valencia Late’ sweet oranges grown on three rootstocks in eastern Mediterranean

Abstract: The plant growth, yield, yield efficiency, and fruit quality of 'Rhode Red Valencia' and 'Valencia Late' sweet oranges (Citrus sinensis (L.) Osbeck) on three rootstocks were evaluated under Eastern Mediterranean climatic conditions of Dörtyol-Hatay, which is one of the oldest and largest citrus and mandarin (Citrus reticulata Blanco) production regions in Turkey. The fruit yield was affected by rootstock in both scion cultivars from 2007 through 2010. Trees on 'Troyer' citrange had lower yield than those budde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
4
9
0
2
Order By: Relevance
“…The scion/rootstock ratio (SRR) was statistically similar in all treatments, although the most favorable rootstocks were the 'Cleópatra' mandarin, LVK x LCR-038, and the 'Santa Cruz' Rangpur lime (Table 1). Similar results were obtained for 'Valência Rhode Red' and 'Valência Late' (Yildiz et al, 2013). No symptoms associated with grafting incompatibility were observed during the evaluation period in the present study.…”
Section: Resultssupporting
confidence: 89%
“…The scion/rootstock ratio (SRR) was statistically similar in all treatments, although the most favorable rootstocks were the 'Cleópatra' mandarin, LVK x LCR-038, and the 'Santa Cruz' Rangpur lime (Table 1). Similar results were obtained for 'Valência Rhode Red' and 'Valência Late' (Yildiz et al, 2013). No symptoms associated with grafting incompatibility were observed during the evaluation period in the present study.…”
Section: Resultssupporting
confidence: 89%
“…A similar behavior was observed in most selected rootstocks, which was interestingly not related to the tree size class. The rootstock influences on the alternate bearing of the scion variety under water deficit conditions, with variations higher than 50% in some late sweet orange varieties (Yildiz, Demirkeser, & Kaplankiran, 2013;Cantuarias-Avilés, Mourão Filho, Stuchi, Silva, & Espinoza-Núñez, 2011). Considering the scenario of constraining climate change and limited water supply for citrus irrigation in the major producing regions (Fares, Bayabil, Zekri, Mattos Junior, & Awal, 2017;Carr, 2012), the breeding of rootstocks that use water more efficiently or tolerate seasonal drought will become determinant for the sustainability of the citriculture on condition that high yield of high quality fruits will remain as main selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Cantuarias-Aviles et al (2010), when comparing 'Okitsu' tangerine fruits grafted on 12 rootstocks, found that 'Flying Dragon' induced higher TA and SS values, whereas 'Cravo Limeira' and 'Cravo FCAV' limes induced higher precocity and lower FQ. Yildiz et al (2013), while evaluating rootstock effect on 'Valencia Late' and 'Rhode Red Valencia' orange tree fruit quality in Dörtyol-Hatay, Turkey, obtained higher fresh fruit mass for 'Valencia Late' when it was grafted on 'Carrizo', and there were no fresh fruit mass differences for 'Rhode Red Valencia'. On the other hand, according to the authors, there was no rootstock effect on juice percentage, number of seeds per fruit, TA and SS/TA ratio.…”
Section: Rootstockmentioning
confidence: 99%